Pockets of hope; studies of land and people - Munzer, Martha E.; Conservation Foundation (New York : Alfred A. Knopf, 1967)
Studies of five economically depressed areas: Pennsylvania coal fiel ds, iron areas of upper Michigan, watersheds of Tennessee, Pueblo India n reservations of the Southwest, and underdeveloped resources of Alaska . Examines the history of land use and misuse of each region and presen ts programs for land, community, and resources development.
Includes Bibliographical references: ( p. 203-204) and index.
Keywords: Natural resources -- United States -- Case studies; Natural resources -- Case studies